PENGARUH EDUKASI TENTANG PENYAKIT MENULAR SEKSUAL (PMS) TERHADAP PENGETAHUAN DAN SIKAP PELAJAR SMAN 3 BANJARMASIN - Dhio Husmawan Az’har; Noor Muthmainah; Nika Sterina Skripsiana; Farida Heriyani; Nani Zaitun (Homeostasis, 2022)
Sexually Transmitted Diseases (STDs) are infections that are transmitted from one individual to another primarily through sexual contact. The purpose of this study was to determine the effect of Sexually Transmitted Diseases (STD) education on the knowledge and attitudes of SMAN 3 Banjarmasin students. This research design uses a pre-experimental design with one group pretest and posttest design. The sample is 86 people who are students of SMAN 3 Banjarmasin. The research instrument used a questionnaire given before or after education. The sampling technique used was proportional strafied random sampling and analyzed using the Wilcoxon test. The results of this study indicate that there is a significant difference in knowledge and attitudes before (pretest) and after (posttest) education with p = 0.00. It can be concluded that there are differences in the knowledge and attitudes of SMAN 3 Banjarmasin students before and after education